Kapang Endofitik Tanaman Brucea javanica (L.) Merr yang Berpotensi menghasilkan Enzim Xilanase - Wibowo Mangunwardoyo; Shirly Kumala; I. G.A. Ayu Wiratih (JURNAL ILMU KEFARMASIAN INDONESIA, 2006)
Xylanase enzyme activity of endophytic fungi from Brucea javanica (L.) Merr has been done. Fruit, leave and stem of the plant collected from Bogor, Cianjur, and Tawangmangu which used in this study. To evaluate the enzyme activity the endophytic fungi isolate were inoculated on PDY medium and fermented at room temperature, shake at 150 rpm for 14 days. The supernatan were used to examine the extracellular enzyme and the biomass for intracellular enzyme. The DNS methods was used to test the enzyme activity. The results showed isolate 1.1.8; 1.2.17; 1.3.16 and 1.3.6 produced intra and extracellular xylanase enzyme. Isolate 1.1.6 produced only extracellular enzyme while isolate 1.2.2 did not produce both intra and extracellular enzyme.